Increase Employee Retention: Impact Work-Life Balance, Meaningful Work, and Job Satisfaction Towards Turnover Intention - Angelyn Kuancintami; Andreas Heryjanto (CV. Publikasi Indonesia, 2023)
This study aims to examine the impact of work-life balance and meaningful work on turnover intention, with the mediating role of job satisfaction among employees at PT. Spectrum UniTec. The probability sampling technique with a simple random sampling approach was used to obtain 246 employee samples in PT. Spectrum UniTec Tangerang. Data were analyzed using the SEM-PLS method. This empirical study reveals that work-life balance, meaningful work, and job satisfaction have a significant negative impact on turnover intention. Meanwhile, work-life balance and meaningful work have a significant positive influence on job satisfaction. This empirical study also indicates that job satisfaction mediates the relationship between work-life balance and meaningful work on turnover intention. This study examines work-life balance, meaningful work as predictors of turnover intention, and confirms that job satisfaction is a mediating variable between meaningful work and work-life balance on turnover intention.Companies can pay attention to and create a work environment that supports employees' work-life balance, helps employees find meaning in their work, and enhances employee job satisfaction as efforts to reduce turnover intention. This research can enhance understanding of how factors like work-life balance, meaningful work, and job satisfaction interact and influence turnover intention